Factors associated with the perception of problems presented in medical consultation in four cities of Peru - Astocondor-A., Jhonny (2016)
Objetive: The aim of the study was to determine the factors associated with the perception of problems presented in medical consultation in four cities in Peru. Material and methods: Multicenter, analytic and transverse study, carried out between May and June 2015 in hospitals of four Peruvian cities (Lima, Ucayali, Piura and Ica). The PREMEPA scale was used to measure the characteristics of the medical consultation also medical data was recorded. Statistical analysis sought associations and p-values, through generalized linear models. Results: 804 people were surveyed. 57% were women (459); the average age was 45 years (range 26-59). Lima was the city with higher frequency of problems presented during external consultation (35%). In multivariate analysis, the frequency of problems presented during external consultation decreased with a better service (RPa: 0,7; IC95%: 0,6-3,09), better care (RPa: 0,5; IC95%: 0,4-0,6) and explanation from the treating physicians (RPA: 0.7; 95% CI: 0.6-0.8),adjusted whether the doctor was male or female, specialty and having a history of problems with a doctor. Conclusions: It was found that certain characteristics of doctor treatment during consultation can generate the perception of problems by users, so this should be taken into account to generate training and sensitization programs of the various health institutions.